Investigation of the Relationship between Physical Activity and Body Mass Index in Children with Down Syndrome - Çiğdem El; Esra Doğru Hüzmeli; Özden Gökçek (Galenos Yayinevi, 2020)
Aim:This study aimed was to investigate the relationship between physical activity levels and the Body Mass index (BMI) of children with Down syndrome (DS).Materials and Methods:This study included 26 children (15 male, 11 female) with DS. In this study, demographic information was recorded, the physical activity was measured with the Eurofit battery; body fat content, muscle weight, protein content, body fluid ratio and basal metabolic rate were measured by Bioelectric Impedance Analysis.Results:The mean age of the participants was 10.96±2.94 years and the mean BMI of the participants was 21.51±6.719. There was moderate correlation between general fat weight and arm motion speed (r=0,40); moderate correlation between sit and reach test and general fat weight (r=-0.45), trunk fat weight (r=-0.52), liquid ratio (r=0.54); moderate correlation between basal metabolic rate and right hand grip strength (r=0.73), right arm weight without fat (r=0.70), right arm muscle weight (r=0.69), basal metabolic rate (r=0.73); left hand grip muscle with left arm muscle weight (r=0.74), left arm weight without fat (r=0.75), basal metabolism rate (r=0.72), mineral amount (r=0.83), amount of protein (r=0.83); moderate correlation between thirty-second shuttle and body fat percentage (r=-0.44), liquid ratio (r=0.45), body density (r=0.46); moderate correlation between twisted arm hanging strength and fat rate in arm (r=-0.47) with trunk fat rate (r=-0.40), fat weight (r=-0.39); moderate correlation between twenty-meter resistance and trunk fat rate (r=-0.40).Conclusion:It was seen that the physical activity level decreased as the fat ratio increased in individuals with DS. Basal metabolic rate, fluid ratio, and physical activity were found to be correlated.